2014
DOI: 10.1097/qai.0b013e31829ceb14
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Early Mortality on Antiretroviral Therapy for Adults in Rural South Africa Since Change in CD4+ Cell Count Eligibility Criteria

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 31 publications
5
26
0
Order By: Relevance
“…Antiretroviral therapy was made available to patients with CD4 counts less than 200 cells per μL through public-sector primary health-care clinics in September, 2004. Treatment eligibility was extended to patients with CD4 counts of less than 350 cells per μL for pregnant women and patients with active tuberculosis in April, 2010, and then for all adult patients in August, 2011 27 . Antiretroviral therapy coverage of all HIV-infected people in the study area rose from 0% in 2004 to 31% in 2011 26 …”
Section: Methodsmentioning
confidence: 99%
“…Antiretroviral therapy was made available to patients with CD4 counts less than 200 cells per μL through public-sector primary health-care clinics in September, 2004. Treatment eligibility was extended to patients with CD4 counts of less than 350 cells per μL for pregnant women and patients with active tuberculosis in April, 2010, and then for all adult patients in August, 2011 27 . Antiretroviral therapy coverage of all HIV-infected people in the study area rose from 0% in 2004 to 31% in 2011 26 …”
Section: Methodsmentioning
confidence: 99%
“…In our study, the main causes of clinical deterioration in patients were TB, PCP, CNS complications, malignant tumors, sepsis, and decompensated liver cirrhosis. Clinicians should strive to diagnose HIV and initiate ART earlier, which have been shown to potentially decrease short-term mortality by 46% (29).…”
Section: Discussionmentioning
confidence: 99%
“…Active TB among HIV-infected patients, even if successfully treated, seems to increase the number of deaths (9). Recent changes made in the eligibility criteria for receiving ART, using a higher CD4+ T-cell count cut-off, have resulted in a significant reduction in early mortality rates in South Africa (10). However, patients in China usually do not undergo HIV testing before contracting opportunistic infections (OIs).…”
Section: Introductionmentioning
confidence: 99%
“…As of the end of 2013, some 11.7 million adults and children were estimated to be on ART 1 , representing almost two thirds of those eligible for ART under current guidelines 2 . Recent studies have observed large reductions in mortality and corresponding increases in life expectancy in some of the hardest hit countries and populations 3,4 .…”
Section: Introductionmentioning
confidence: 99%